2017
DOI: 10.1111/mec.14064
|View full text |Cite
|
Sign up to set email alerts
|

Nesting habits influence population genetic structure of a bee living in anthropogenic disturbance

Abstract: While most organisms are negatively affected by anthropogenic disturbance, a few species thrive in landscapes altered by humans. Typically, native bees are negatively impacted by anthropogenic environmental change, including habitat alteration and climate change. Here, we investigate the population structure of the eastern carpenter bee Xylocopa virginica, a generalist pollinator with a broad geographic range spanning eastern North America. Eastern carpenter bees now nest almost exclusively in artificial woode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 79 publications
1
19
0
Order By: Relevance
“…For example, we found that urban fragmentation can result in increased genetic drift and reduced gene flow for many organisms including both small (Gortat et al, ) and large mammals (Wilson, Farley, McDonough, Talbot, & Barboza, ), lizards (Delaney et al, ), amphibians (Hitchings & Beebee, ), fish (Mather, Hancox, & Riginos, ), insects (Keller, Nentwig, & Largiader, ) and plants (Hollingsworth & Dickson, ). Urban facilitation, however, resulted in reduced drift and increased gene flow in a variety of organisms including insects (Kamdem, Fouet, Gamez, & White, ; Vickruck & Richards, ), birds (Tang et al, ), mammals (Adams, van Heezik, Dickinson, & Robertson, ) and plants (Johnson, Prashad, Lavoignat, & Saini, ). Indeed, a wide variety of taxa also experienced no change in genetic drift and gene flow, including organisms as diverse as plants (Culley, Sbita, & Wick, ) and mammals (Atterby, Allnutt, MacNicoll, Jones, & Smith, ).…”
Section: Joint Effects Of Urbanization On Genetic Drift and Gene Flowmentioning
confidence: 99%
“…For example, we found that urban fragmentation can result in increased genetic drift and reduced gene flow for many organisms including both small (Gortat et al, ) and large mammals (Wilson, Farley, McDonough, Talbot, & Barboza, ), lizards (Delaney et al, ), amphibians (Hitchings & Beebee, ), fish (Mather, Hancox, & Riginos, ), insects (Keller, Nentwig, & Largiader, ) and plants (Hollingsworth & Dickson, ). Urban facilitation, however, resulted in reduced drift and increased gene flow in a variety of organisms including insects (Kamdem, Fouet, Gamez, & White, ; Vickruck & Richards, ), birds (Tang et al, ), mammals (Adams, van Heezik, Dickinson, & Robertson, ) and plants (Johnson, Prashad, Lavoignat, & Saini, ). Indeed, a wide variety of taxa also experienced no change in genetic drift and gene flow, including organisms as diverse as plants (Culley, Sbita, & Wick, ) and mammals (Atterby, Allnutt, MacNicoll, Jones, & Smith, ).…”
Section: Joint Effects Of Urbanization On Genetic Drift and Gene Flowmentioning
confidence: 99%
“…Urbanization can influence gene flow by either creating barriers, such as roads and habitat fragmentation that reduce gene flow (Holderegger and Di Giulio, 2010;Storfer et al, 2010), or habitat corridors and human-mediated dispersal that increase gene flow (Crispo et al, 2011;Arredondo et al, 2018;Miles et al, 2018a,b). Perhaps unsurprisingly, urbanization more frequently reduces gene flow for herbivorous arthropods (Desender et al, 2005;Davis et al, 2010;Schoville et al, 2013;López-Uribe et al, 2015;Vickruck and Richards, 2017) than it elevates it (Keller et al, 2004;Desender et al, 2005;Dronnet et al, 2005). In fact, when calculating the mean pairwise differentiation from the studies that measured the degree of population structure (N = 6; Supplemental Table 1), which is directly affected by the amount of gene flow, there is slightly higher and more variable genetic differentiation (measured by the fixation index F ST ) between urban populations than between non-urban populations; however, this trend is not significant [t (5) = 1.24, p = 0.26; Figure 4A].…”
Section: Adaptive and Non-adaptive Evolutionmentioning
confidence: 99%
“…Similarly, urbanization typically increases the importance of genetic drift, due to habitat loss that reduces the total population size and fragmentation that reduces local population sizes and restricts gene flow, all of which can reduce the effective population size (N e ) (Johnson and Munshi-South 2017). This increased genetic drift results in reduced genetic diversity within urban populations of herbivorous arthropods (Keller et al, 2004;Desender et al, 2005;Vandergast et al, 2009;Schoville et al, 2013;López-Uribe et al, 2015;Vickruck and Richards, 2017). There is 18% less genetic diversity, measured as observed heterozygosity (H O ), in urban compared to nonurban populations across the studies that measured genetic diversity (N = 8); however, this trend is also non-significant [t (7) = 1.19, p = 0.27; Supplemental Table 1; Figure 4B].…”
Section: Adaptive and Non-adaptive Evolutionmentioning
confidence: 99%
“…With the exception of Proxylocopa species, which nest in the soil, Xylocopa species nest in dead wood, hollow stalks and bamboo [ 3 , 7 , 20 – 22 ]. The preferred nesting location and substrate have an impact on the distribution and genetic structure of Xylocopa populations [ 11 , 23 , 24 ]. In addition, the diameter of the nesting substrate and nesting substrate resources define the nest structure of carpenter bees [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%